2006
DOI: 10.4314/njsr.v7i1.12281
|View full text |Cite
|
Sign up to set email alerts
|

Uterine leiomyomata: a five year clinicopathological review in Zaria, Nigeria

Abstract: Background: Uterine Leiomyomata (uterine fibroids) are common gynaecologic conditions affecting mainly women in the reproductive age group. Fibroids are associated with many other distressing gynaecologic conditions like menorrhagia, infertility, lower abdominal swelling and discomfort. Methods: This is a retrospective clinicopathological analysis uterine leiomyomata a five-year period (1996-2000). The information required was retrieved from histology bench books and request cards. Results: 209 cases were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 3 publications
2
19
1
Order By: Relevance
“…A study in Enugu showed that 60% of patients with symptomatic uterine fibroid had myomectomy while 36.8% had hysterectomy [2]. These values were similar to findings in Zaria which showed that 62.7% of patients with symptomatic uterine fibroid had myomectomy while 37.3% had hysterectomy [3]. Those who had myomectomy were mainly women who were still desirous of pregnancy.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…A study in Enugu showed that 60% of patients with symptomatic uterine fibroid had myomectomy while 36.8% had hysterectomy [2]. These values were similar to findings in Zaria which showed that 62.7% of patients with symptomatic uterine fibroid had myomectomy while 37.3% had hysterectomy [3]. Those who had myomectomy were mainly women who were still desirous of pregnancy.…”
Section: Introductionsupporting
confidence: 73%
“…Uterine fibroids affect predominantly women in their third and fourth decades of life [1], who are mostly nulliparous; studies carried out in Ilorin and Zaria showed that of women who had uterine fibroids, 60.8% and 60.6% were nulliparous [1,3]. The role of oestrogen in the aetiology of fibroid explains why age and parity may be a risk factor in the development of uterine fibroid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The incidence of these changes and variants are similar to other publications where a large number leiomyomas were studied. 5,6,7,8 Hyaline change and calcification are usually seen in long standing leiomyomas and do not pose significant IJBR (2013) 04 (12) www.ssjournals.com diagnostic problems.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the late presentation, most of these women, when they finally accept surgery and have been able to raise the money for the surgery seek to have abdominal myomectomy despite counseling and despite the risk associated with such a surgery instead of opting for the less risky hysterectomy because of their desire to conserve their reproductive potential [16,17]. Extensive abdominal myomectomy is associated with prolonged anesthesia and surgery times, increased risk of hemorrhage, sepsis, thromboembolism, uterine synechia, intraperitoneal adhesions and intestinal obstruction [3,[18][19][20].…”
Section: Challenges Of Managementmentioning
confidence: 99%